POLITIK UANG DALAM PEMILIHAN KEPALA DESA (STUDI KASUS DI DESA PAYUNG SEKAKI KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU TAHUN 2018) - Abu Bakar; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The high motivation of the community to occupy the position of village head tends not to be matched by an increase in their capacity and quality to fill the village head's position. As a result, candidates who advance in the nomination of the Village Head often do various ways to win themselves even though by means of which is actually prohibited in the election regulations. Money Politics that occurred in the Payung Sekaki Village Pilkades turned out to be varied in each Hamlet and RT in Payung Sekaki Village, ranging from 200 thousand to 150 thousand. The money came from the Suskes Team, one of the candidates. From the results of this study it can be seen that money politics in the Pilkades, namely in the form of Sound Purchases conducted by candidates for the Village Head of Payung Sekaki ranges from Rp. 150,000-Rp. 200,000 per person. Provision of Personal Items carried out by each prospective Village Head is very important, both in the form of groceries, spending money, in addition to the services and activities of each candidate is to assist in the management of KTP and Permits in the issuance of Electrical Installation for the community, and who the last is giving group items, namely in the form of batik clothes, recitation mothers' uniforms, prayers, and for poison / dopra spray for Payung Sekaki Village community. Factors that influence the occurrence of Money Politics consist of internal factors and external factors, internal factors include the Voter Data Collection Factor where there is an increase in DPT that is not in accordance with the Domicile, and there are some people who are not registered to vote. The Voting Factor, namely the real occurrence of money politics by the Candidates of the Village Head, as well as the Election Committee and TPS supervision factors, is the occurrence of weaknesses of the committee and supervisors in carrying out their duties. External factors consist of economic factors and the lack of political knowledge of the people in Payung Sekaki Village. Keywords: Money Politics, Village Head Election, Payung Sekaki Village